The Effect of Combining Myofascial Release with Ice Application on a Latent Trigger Point in the Forearm of Young Adults: A Randomized Clinical Trial. Issue 3 (2nd October 2015) - Gutiérrez-Rojas, Cristian; González, Ignacio; Navarrete, Elías; Olivares, Evelyn; Rojas, José; Tordecilla, Diego; Bustamante, Carlos
Abstract: Background: Myofascial trigger points (MTrP) are considered to be a common source of pain in people. Due to their presence in any skeletal muscle in the body, they can be relevant in the genesis of musculoskeletal disorders. Their preventive management could reduce its potential activation and impact over people's functioning. Objectives: The aim was to determine the immediate effect of combining myofascial release (MFR) with ice on a latent MTrP in the forearm of young adults. Materials and methods: Using a randomized repeated measures design, 30 young adults with one latent MTrP on the extensor muscles of the forearm were allocated into three groups; group I received ice massage, group II received MFR and group III received MFR with ice. The pressure pain threshold (PPT), pressure pain perception (PPP) and strength of the flexor and extensor muscles of the forearm were evaluated at baseline, immediately after treatment and at 30 min. Results: An immediate improvement in PPT ( p   < 0.05) and PPP ( p   <  0.0005) occurred in group III. Additionally, an increase in flexor muscle strength ( p   <  0.05) is observed 30 min in this group. Group II increased its PPT immediately ( p   <  0.005) and afterwards ( p  < 0.05). Group I also changed its PPP immediately ( p  < 0.005). No changes in extensor muscle strength were observed. Conclusions: The results demonstrate an immediate improvement in pain variables after the application of ice massage, MFR and MFR with ice in young adults with a latent MTrP.